Ptychographic coherent x-ray diffractive imaging in the water window - Giewekemeyer, Klaus; Beckers, Mike; Gorniak, Thomas; Grunze, Michael; Salditt, T.; Rosenhahn, Axel (Optics express, 2011)
Coherent x-ray diffractive microscopy enables full reconstruction of the complex transmission function of an isolated object to diffraction-limited resolution without relying on any optical elements between the sample and detector. In combination with ptychography, also specimens of unlimited lateral extension can be imaged. Here we report on an application of ptychographic coherent diffractive imaging (PCDI) in the soft x-ray regime, more precisely in the so-called water window of photon energies where the high scattering contrast between carbon and oxygen is well-suited to image biological samples. In particular, we have reconstructed the complex sample transmission function of a fossil diatom at a photon energy of 517 eV. In imaging a lithographically fabricated test sample a resolution on the order of 50 nm (half-period length) has been achieved. Along with this proof-of-principle for PCDI at soft x-ray wavelengths, we discuss the experimental and technical challenges which can occur especially for soft x-ray PCDI.
Gesehen am 22.06.2022